Ilustres senhoras de romances: as leitoras de José de Alencar - Silva, Edinage Maria Carneiro da (2012)
The urban novels of José de Alencar usually bring scenes where women read the works of fiction in vogue in the nineteenth century. Moreover, it is common to the attitude of male narrators address themselves directly to implied readers. José de Alencar was trying to establish a dialogue between fiction and reality. When he adopts these strategies, the novelist shows his intention to establish a dialogue with the women who read his novels. It‟s a way to conquest them and in the same time to leave to the women right readings. Based on the observation of these facts in the novels Cinco minutos, A viuvinha , Luciola and Diva, we intend to meet Alencar‟s some empirical readers, women who lived during the second half of the nineteenth or the beginning of the twentieth. So our study relies on the aesthetics of reception. We will find some women Alencar‟s readers through memorialistic texts of them. Then we can say that the writer was speaking as the spokesman of the social system which he was part and he was placed in position of someone who indicated women readings.